Union of South Africa. Debates of the House of Assembly Third Session, Fifth Parliament 1926 - South Africa Parliament (Cape Town Government Printer, 1926)
Debates of the House of Assembly of the Union of South Africa as reported in the Cape Times. South Africa Politics and government
Debates of the House of Assembly (Hansard). Fourth Session, 4th Parliament, vol. 1 (25 Jan.-10 Apr. 1924)-4th Session, 12th Parliament, v. 108 (1 May-26 May 1961).
Keywords: Union of South Africa; Debates; House of Assembly; Third Session -Fifth Parliament; JC044667; 1926; vol 6; January to June; March; Index to Subject